Innovations in Mobile Educational Technologies and Applications
DOI: 10.4018/978-1-4666-2139-8.ch009
|View full text |Cite
|
Sign up to set email alerts
|

Listening to an Educational Podcast While Walking or Jogging

Abstract: The advent of podcasting offers opportunities for students to learn while performing another activity. While podcasting is advocated by many as helping to learn anywhere and anytime, research indicates that it is not so easy for people to do two things at the same time. Two experiments were set up to examine the effect of performing a secondary task while learning with an iPod. In the experimental groups, the participants had to combine a learning task (listening to an educational podcast) with a secondary tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In regards to audio-only media specifically, a study by Doolittle and Mariano found that students in a stationary position outperformed students in a mobile environment when using a portable digital media player [ 27 ]. However, Coens and colleagues conducted two studies with conflicting results regarding podcast usage and performing a secondary task while learning [ 28 ]. In the current study, even though students were more likely to be multitasking when listening to podcasts, their final post-intervention results were comparable to the blog post group.…”
Section: Discussionmentioning
confidence: 99%
“…In regards to audio-only media specifically, a study by Doolittle and Mariano found that students in a stationary position outperformed students in a mobile environment when using a portable digital media player [ 27 ]. However, Coens and colleagues conducted two studies with conflicting results regarding podcast usage and performing a secondary task while learning [ 28 ]. In the current study, even though students were more likely to be multitasking when listening to podcasts, their final post-intervention results were comparable to the blog post group.…”
Section: Discussionmentioning
confidence: 99%
“…The ambient conditions can constrain certain work activities when traveling in a vehicle, as reported by mobile knowledge workers (e.g., Hislop, 2012 ). Learning via listening to podcasts is possible while the learner is physically moving (walking or jogging), but learning is less effective than when sitting ( Coens et al, 2011 ). Text input performance was reduced when the mobile device user was walking ( Musić and Murray-Smith, 2016 ).…”
Section: Proposed Conceptual Frameworkmentioning
confidence: 99%
“…Previous studies have focussed on the educational opportunities offered by small mobile devices, such as the iPod (Mahruf et al 2010;Coens et al 2011), mobile phones, smartphones (Seppälä and Alamäki 2003;Aubusson et al 2009;Ekanayake and Wishart 2014), and tablets (Kearney and Maher 2013;Bates and Martin 2013;Hargis et al 2013;Hashim 2014), as well as combined situations in which various types of devices have been used (Järvelä et al 2007;Husbye and Elsener 2013;Herro et al 2013;Şad and Göktaş 2014). The participants involved in these studies are inservice or pre-service teachers, teacher educators, administrative staff, teacher advisors or developers.…”
Section: Theoretical Frameworkmentioning
confidence: 99%